Green synthesis of silver nanoparticles using Eranthemum Pulchellum (Blue Sage) aqueous leaves extract: Characterization, evaluation of antifungal and antioxidant properties - Prakash J.; Shekhar H.; Yadav S.; Dwivedy A.; Patel V.; Tiwari S.; Vishwakarma N. (My University, 2025)
Background: Nanoparticles modulate several physiochemical and biological properties. In this regard, silver nanoparticles (AgNPs) have shown remarkable applications. The present research work comprises green synthesis of AgNPs using aqueous leaves extract of Eranthemum pulchellum and evaluation of its efficacy as antifungal and antioxidant agents. Methods: Synthesized AgNPs have been characterized by Fourier Transforms Infrared (FTIR) Spectroscopy, X-ray diffraction (XRD), transmission electron microscopy (TEM), and ultraviolet-visible spectrophotometry. Qualitative phytochemical analysis of aqueous leaves extract of E. pulchellum and FTIR spectrum of the synthesized AgNPs suggest about the presence of different phytochemicals and functional groups, respectively, which are responsible for reducing silver ions as well as capping and stabilizing synthesized nanoparticles. Results: The wavelength of maximum absorbance of AgNPs solution near to 439 nm indicates the spherical morphology. XRD infers about average crystalline size of the synthesized AgNPs to be ~12 nm. Selected area electron diffraction pattern of the synthesized AgNPs shows four visible diffraction rings corresponding to (111), (200), (220), and (311) set of planes which are attributed to face centered cubic metallic silver. The size and spherical shape of the synthesized AgNPs have been further determined by TEM. The synthesized AgNPs have shown a significant antifungal activity against Aspergillus flavus (AF-LHP-NS7) strain with minimum inhibitory concentration value of 200 μg/mL. The synthesized AgNPs have also shown strong antioxidant efficacy through Azino-bis-3-ethylbenzothiazoline-6-sulfonic acid assay with IC50value of 462.56 μg/mL. Conclusions: The present study shows a green and facile synthesis of AgNPs. Leaves extract of E. pulchellum has been first time utilized as efficient reductant for the AgNPs synthesis. These AgNPs have shown potent antifungal and antioxidant activity. © 2021 Medknow. All rights reserved.